Genome-wide investigation of the bZIP transcription factor gene family in Prunus mume: Classification, evolution, expression profile and low-temperature stress responses - Ping Li; Tangchun Zheng; Lulu Li; Jia Wang; Tangren Cheng; Qixiang Zhang (Horticultural Plant Journal, 2022)
Prunus mume is an important woody plant that has high ornamental and economic value, widely distributed and used in landscape architecture in East Asia. In plants, basic (region) leucine zipper (bZIP) transcription factors play important regulatory roles in growth, development, dormancy and abiotic stress. To date, bZIP transcription factors have not been systematically studied in P. mume. In this study, 49 bZIP genes were first identified in P. mume, and the PmbZIP family was divided into 12 groups according to the grouping principles for the Arabidopsis thaliana bZIP family. For the first time, we constructed a detailed model of the PmbZIP domains (R-x3N-x7-R/K-x2-K-x6-L-x6-L-x6-L). Phylogenetic and synteny analyses showed that PmbZIPs duplication events might have occurred during the large-scale genome duplication events. A relatively short time of speciation and the finding that 91.84% of the bZIP genes formed orthologous pairs between P. mume and Prunus armeniaca provided evidence of a close relationship. Gene expression patterns were analysed in different tissues and periods, indicating that PmbZIP genes with the same motifs exhibited similar expression patterns. The gene expression results showed that PmbZIP31/36/41 genes played a more prominent role in the response to freezing stress than cold stress. The expression level of almost all subset III genes was upregulated under freezing treatment, especially after cold exposure. We analysed the gene expression patterns of PmbZIP12/31/36/41/48 and their responses to low-temperature stress, which provided useful resources for future studies on the cold/freezing-tolerant molecular breeding of P. mume.